2021
DOI: 10.1136/bmjopen-2020-044196
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based acute care in the last 30 days of life among patients with chronic disease that received early, late or no specialist palliative care: a retrospective cohort study of eight chronic disease groups

Abstract: ObjectiveFor eight chronic diseases, evaluate the association of specialist palliative care (PC) exposure and timing with hospital-based acute care in the last 30 days of life.DesignRetrospective cohort study using administrative data.SettingAlberta, Canada between 2007 and 2016.Participants47 169 adults deceased from: (1) cancer, (2) heart disease, (3) dementia, (4) stroke, (5) chronic lower respiratory disease (chronic obstructive pulmonary disease (COPD)), (6) liver disease, (7) neurodegenerative disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
2
10
1
1
Order By: Relevance
“…We retrospectively evaluated health care utilization in the last year of life by individuals with neurodegenerative movement disorders Compared with published data on individuals who died of cancer in Calgary, Alberta, we found that fewer individuals with neurodegenerative movement disorders received specialist palliative care (17% vs 86%). 7 Those with neurodegenerative movement disorders had lower rates of hospitalbased acute care in the last 30 days of life: 6.8% had more than one ED visit vs 11% of those with cancer, and 16.1% spent >14 days in hospital compared with 25% of those with cancer. The rate of death in hospital for those with neurodegenerative movement disorders in our study was 45.9%, compared with 41% of individuals who died of cancer.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We retrospectively evaluated health care utilization in the last year of life by individuals with neurodegenerative movement disorders Compared with published data on individuals who died of cancer in Calgary, Alberta, we found that fewer individuals with neurodegenerative movement disorders received specialist palliative care (17% vs 86%). 7 Those with neurodegenerative movement disorders had lower rates of hospitalbased acute care in the last 30 days of life: 6.8% had more than one ED visit vs 11% of those with cancer, and 16.1% spent >14 days in hospital compared with 25% of those with cancer. The rate of death in hospital for those with neurodegenerative movement disorders in our study was 45.9%, compared with 41% of individuals who died of cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Early palliative care was defined as beginning ≥90 days before death, a cut point commonly used in the palliative care literature. 7,8…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We asked patients to trade-off life extension with health care cost- “ If you had to make a choice now, would you prefer treatment that extends life as much as possible, or would you want treatment that costs you less?” Patients responded on scale of 1 to 9, with 1 representing - extend life as much as possible at high cost and 9 representing no life extension at less cost. Responses were classified as maximal life extension [ 1 4 ], moderate life extension [ 5 ] and no life extension [ 6 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Global advancements in cancer treatments have led to more than 50% of patients being treated aggressively [ 1 6 ] in some developed countries during their last month of life with 30 to 50% dying in the hospital [ 1 , 2 , 4 8 ]. This is concerning because such care represents low value for the health system, is often inconsistent with patients’ and caregivers’ end-of-life (EOL) preferences and negatively influences caregivers’ perceptions of quality of EOL care received, thereby making adjustment difficult during bereavement [ 7 , 9 – 14 ].…”
Section: Introductionmentioning
confidence: 99%